2021
DOI: 10.3389/fneur.2020.562218
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegenerative Disease and the Experience of Homelessness

Abstract: Introduction: Today, half of the American homeless population is older than 50 years of age. This shift in age distribution among people experiencing homelessness has challenged our long-held views of the causes of homelessness. Age-related neurological diseases, especially neurodegenerative diseases of the brain (NDDB), may play a role eliciting homelessness in a significant proportion of vulnerable older adults. This article aims to explore relationships between homelessness and NDDB in a cohort of research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…We found a high prevalence of socioemotional processing deficits, as well as signs of executive dysfunction and associative memory dysfunction. These deficits provide evidence for frontotemporal lobar dysfunction, in agreement with findings from our retrospective study on homelessness among persons with NDDB (8). Moreover, our study results also suggest a relative sparing of parieto-occipital lobe functions, based on both history and neuropsychological testing.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We found a high prevalence of socioemotional processing deficits, as well as signs of executive dysfunction and associative memory dysfunction. These deficits provide evidence for frontotemporal lobar dysfunction, in agreement with findings from our retrospective study on homelessness among persons with NDDB (8). Moreover, our study results also suggest a relative sparing of parieto-occipital lobe functions, based on both history and neuropsychological testing.…”
Section: Discussionsupporting
confidence: 91%
“…Although lack of longitudinal data, including reliable informants, and lack of brain health biomarkers greatly limited our ability to characterize these individuals more precisely, we found that the signs and symptoms elicited from our participants based on detailed history and neuropsychological testing conformed mostly to AD and FTLD syndromes, whereas other neurodegenerative syndromes such as PD, progressive supranuclear palsy, corticobasal syndrome, and primary progressive aphasia, were less common in our study. These findings support our prior study results (8) and our overarching hypothesis that frontotemporal neurocognitive syndromes are prevalent in older adults experiencing homelessness.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Like mental illness, these conditions are disproportionately higher among incarcerated individuals and linked to increased risk of dementia and neurodegenerative diseases. 13,23,28 Experiencing preincarceration TBI or homelessness may indicate an early-onset clinical phenotype of dementia.…”
Section: Discussionmentioning
confidence: 99%